1-Isoquinolinyl phenyl ketone as a corrosion inhibitor: A theoretical study. (2021) - Abdul Hussein, Ennas; Fanfoon, Dunya Y.; Al-Uqaily, Raheem A.H.; Salman, Ali M.; Kadhim, Mustafa M.; Salman, Abbas W.; Abbas, Zaid M.
Abstract: The compound 1-Isoquinolinyl phenyl ketone (1IPK) was studied theoretically as a corrosion inhibitor by quantum mechanics calculations and docking models. Density functional theory (DFT) of B3LYP/6-311G (d, p) and parameterization model 3 (PM3) using the Gaussian-09 and CASTEP programs was also employed to discuss the inhibition ability. Molecular graphic laboratory (MGL) tools program and discovery studio visualizer (DSV) used to estimate the ability for inhibition Acidithiobacillus Ferrooxidans (AF) bacteria, which is responsible for the corrosion. The calculations of physical properties and quantum chemical parameters correlated to the inhibition efficiency and discussed at the equilibrium geometry. The results indicated that the 1-Isoquinolinyl Phenyl Ketone could be adsorbed on the mild steel surface firmly through the nitrogen atom on the isoquinoline rings and the carbonyl group. Besides, the moderate values of parameters describe the low-efficiency of inhibition in acidic and saline medium. Total electron density (TED) and electrostatic surface potential (ESP) Figures showed the active site that is involved in the inhibition processes. In addition, the adsorption types were studied by different parameters.